Characterization of Syndiotactic Polystyrene Nanofilms by PM‐IRRAS Spectroscopy. Issue 1 (January 2016) - Daniel, Christophe; Lardone, Margherita
Summary: Nano syndiotactic polystyrene (s‐PS) films prepared by casting and spin‐coating of diluted solutions have been characterized by Polarization Modulated Infra‐red Reflection Absorption Spectroscopy (PM‐IRRAS). In this work it will be shown that PM‐IRRAS allows a complete characterization of s‐PS nanofilms polymorphism. In particular PM‐IRRAS is not only capable to investigate the polymeric chain conformational ordering but is also sensible to the crystalline chain packing. It will be also shown that PM‐IRRAS allows the study of uniplanar orientation obtained in s‐PS nanofilms.